FENOMENA SOSIAL JARIMAH KHALWAT DAN SEX BEBAS DI KOTA BANDA ACEH SETELAH PEMBERLAKUAN QANUN NO. 6 TAHUN 2014 TENTANG HUKUM JINAYAT - Amrullah, Amrullah (Universitas Islam Negery Ar-raniry, 2018)
This study discussed the improvement of khalwat and free sex in the city of Banda Aceh after the enactment of qanun No. 6 of 2014 concerning Jinayat Law in Aceh. Based on the field study of the author, there are factors that influence the increase in khalwat and free sex after the enactment of Jinayah qanun. There are communication sophistication, the availability of inexpensive electronic facilities to access pornography, economic problems, an individualistic lifestyle, and the apathetic people. The social phenomena of khalwat and free sex still occur in the city of Banda Aceh, although the Qanun Jinayah already applies.